2010
DOI: 10.1308/003588410x12664192075936
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of blunt abdominal trauma as a cause of acute appendicitis

Abstract: Ann R Coll Surg Engl 2010; 92: 477-482 477Appendicitis is a very common surgical condition. Approximately 7% of people in Western countries have appendicitis at some time during their lives. Obstruction of the proximal lumen of the appendix has long been considered to be the major cause of acute appendicitis. In many cases, the cause of obstruction is unknown. The evidence from temporal and geographical clustering of cases suggests primary infectious aetiology.1 Trauma has been known to be a rare cause of appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Furthermore, a retrocaecal appendix is unlikely to be injured in isolation. Conversely, an appendix lying in an inguinal hernia (Amyand's hernia) can be more vulnerable to injury, allowing blunt trauma to compress the appendix against the underlying pubic bone 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a retrocaecal appendix is unlikely to be injured in isolation. Conversely, an appendix lying in an inguinal hernia (Amyand's hernia) can be more vulnerable to injury, allowing blunt trauma to compress the appendix against the underlying pubic bone 8 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an appendix lying in an inguinal hernia (Amyand's hernia) can be more vulnerable to injury, allowing blunt trauma to compress the appendix against the underlying pubic bone. 8 In cases of injury severity score of less than 4, a multifactor complex mechanism exists. An indirect mechanism of increased intraluminal pressure can play a role to the formation of TA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendicitis following trauma is a rare sequalae. It has been previously reported following blunt abdominal trauma including falls, road traffic accidents, assault, bicycle handle and crush injures [2,3].…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that this is due to the ischaemia that results when the blood vessels get blocked by the sickled red blood cells. Abdominal trauma has also been seen to result in acute appendicitis (Toumi et al, 2010). This is believed to be mediated by processes that result in the obstruction of the appendiceal lumen.…”
Section: The Pathophysiological Mechanisms Of Acute Appendicitismentioning
confidence: 99%